South Asia, growth and regional integration - SAARC Business Conclave 2005 : New Delhi, India); Ahmed, Sadiq; Ghani, Ejaz.; World Bank.; South Asian Association for Regional Cooperation; SAARC Chamber of Commerce and Industry (Delhi : Macmillan, 2007)
Contributed articles presented at the first SAARC Business Conclave held in November 2005 at New Delhi jointly organized by World Bank, SAARC and SCCI.
"The World Bank."
Includes statistical tables.
Includes bibliographical references and index.
Keywords: South Asian cooperation -- Congresses; History; South Asia -- Economic integration -- Congresses; South Asia -- Commercial policy -- Congresses